Volumetric but Not Time Capnography Detects Ventilation/Perfusion Mismatch in Injured Rabbit Lung - Tolnai, József; Fodor, Gergely H.; Babik, Barna; Dos Santos Rocha, André; Bayat, Sam; Peták, Ferenc; Habre, Walid (Frontiers in Physiology, 2018)
Whereas time capnography (Tcap) is routinely displayed during mechanical ventilation, the volumetric representation (Vcap) is seldom used. We compared the diagnostic value of indices derived from Tcap and Vcap following ventilation to perfusion ratio (V ̇⁄Q ̇ ) mismatch subsequent to experimentally induced acute respiratory distress syndrome (ARDS), and alveolar recruitment by elevating the positive end-expiratory pressure (PEEP). Lung injury was induced by iv lipopolysaccharide, whole lung lavage and injurious ventilation in anesthetized, mechanically ventilated rabbits (n=26). Mainstream Tcap and Vcap were performed to assess normalized phase 2 (Sn2T, Sn2V) and phase 3 slopes (Sn3T, Sn3V) in the time and volumetric domains. Vcap was also used to estimate Enghoff’s physiological dead space (VDE). Lung oxygenation index (PaO2/FiO2) and intrapulmonary shunt (Qs/Qt) were derived from arterial and central venous blood gas samples. All measurements were made under baseline conditions, and, following lung injury, under moderate (6 cmH2O) and high PEEP levels (9 cmH2O). Lung injury deteriorated the PaO2/FiO2 (baseline vs. injured 466±10.2 [95% confidence interval] vs. 77.3±17.1 mmHg, p<0.05) and compromised all mechanical parameters significantly, whereas Tcap parameters exhibited contradictory or inconsistent changes. Conversely, Vcap indices exhibited consistent changes and provided excellent diagnostic value in detecting lung-function deterioration subsequent to lung injury (area under the receiver operating characteristic curve of 1.0±0.0, 0.87±0.22 and 0.86±0.22 for VDE, Sn3V and Sn3V/Sn2V, respectively). Elevated PEEP increased PaO2/FiO2 and decreased Qs/Qt, which was reflected only in the Vcap slope ratio (Sn3V/Sn2V, p<0.05). Our findings demonstrate the limited value of Tcap to detect ventilation to perfusion ratio (V ̇⁄Q ̇ ) mismatch, following severe lung injury. Conversely, indices derived from Vcap proved to be sensitive for detecting lung volume loss and alveolar recruitment. Therefore, promotion of Vcap is of paramount importance as a real-time, non-invasive, bedside monitoring modality to detect the development of and to follow-up the progression of lung injury in a model of ARDS.